Support the activities of cotton-textile clusters, carry out a radical reform of the textile, clothing and knitting industry, further increase the export potential of the industry - Khalikov Talibjon Luptullaevich (Journal of Artificial Intelligence and Digital Economy, 2024)
The article explores and discusses simple methods of supporting the activities of cotton-textile clusters, radical reform of the textile and clothing-knitting industry, and the phased implementation of further increasing the export potential of the industry. Practical recommendations have been developed